2020
DOI: 10.1038/s41598-020-68377-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of strain, pressure, and electron correlation on magnetism and crystal structure of Mn2GaC from first-principles

Abstract: the atomically laminated Mn 2 GaC has previously been synthesized as a heteroepitaxial thin film and found to be magnetic with structural changes linked to the magnetic anisotropy. Related theoretical studies only considered bulk conditions and thus neglected the influence from possible strain linked to the choice of substrate. Here we employ first principles calculations considering different exchangecorrelation functionals (PBE, PW91, PBEsol, AM05, LDA) and effect from use of + U methods (or not) combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 63 publications
3
3
0
Order By: Relevance
“…We can observe quite flat bands around the Fermi level and an indirect band gap with the smallest energy transition being from the Γ point to near the K point. Based on the recommended values of the Hubbard correction U for the Mn-based MXenes from previous studies, 45,54,56 we conclude from band structures (Fig. S11, ESI†) and band gaps (Table S3, ESI†) that PBE+ U ( U = 3 eV) corresponds well with a non-empiric SCAN approach without any U correction.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…We can observe quite flat bands around the Fermi level and an indirect band gap with the smallest energy transition being from the Γ point to near the K point. Based on the recommended values of the Hubbard correction U for the Mn-based MXenes from previous studies, 45,54,56 we conclude from band structures (Fig. S11, ESI†) and band gaps (Table S3, ESI†) that PBE+ U ( U = 3 eV) corresponds well with a non-empiric SCAN approach without any U correction.…”
Section: Resultssupporting
confidence: 56%
“…As has been recently shown in multiple studies, even the precursor MAX phase Mn 2 GaC has an AFM ground-state when more complex spin motifs are taken into account. [18][19][20]54 The same result holds even for the clean Mn 2 C sheet, although both the MAX phase and Mn 2 C are conductors. 27,55,56 The semiconducting behavior is therefore only achieved by oxygen termination.…”
Section: Geometrical Structures and Magnetic Solutionssupporting
confidence: 54%
“…We also analysed the epitaxial stress in the epilayer and in the crystallites of the polycrystalline layer of the Fe-Si alloy. Changing the chemical composition within the trilayers based on ferromagnetic Fe x (Si 1− y Ge y ) alloys can be used to tune the epitaxial stress and thereby the electronic structure and, as a result, the functional properties of the material [ 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Novoselova et al [130] observed a first order magnetic phase transition at 214 K from AFM at higher temperatures to a non-collinear AFM spin structure at lower temperatures, with the magnetostriction changing sign at this magnetic phase transition in a Mn 2 GaC film prepared by magnetron sputtering. It has been theoretically proven by Dahlqvist et al [131,132] that the magnetic states and structural parameters of Mn 2 GaC can be manipulated through controlling the temperature, the magnetic field or the applied pressure. The temperature and magnetic field dependence of magnetic properties has also been studied for some solid solutions such as (Cr 0.5 Mn 0.5 ) 2 GaC, (Mo 0.5 Mn 0.5 ) 2 GaC, (Cr 0.5 Mn 0.5 ) 2 AuC, etc [133,134], suggesting new pathways for tuning magnetism of MAX phases.…”
Section: ) Electrical Conductivitymentioning
confidence: 99%
“…Related research to date is still focused on the prediction, discovery and determination of the fundamental magnetic properties of MAX phases and their solid solutions. However, the observed tunability of the magnetic properties by controlling the atomic configuration of alloying atoms on the M-site in simulations, by introducing multiple alloying elements on the A-site in experiments, and by controlling the temperature, the magnetic field or the applied pressure in both simulations and experiments, will guide the development of magnetic MAX phases and their solid solutions with promising properties for electronics, spintronics, refrigeration, etc [6,91,92,[130][131][132][133][134]140].…”
Section: ) Electrical Conductivitymentioning
confidence: 99%